Switchable Adhesion of Hydrogels to Plant and Animal Tissues - Leah K. Borden; Morine G. Nader; Faraz A. Burni; Samantha M. Grasso; Irene Orueta‐Ortega; Mahima Srivastava; Paula Montero‐Atienza; Metecan Erdi; Sarah L. Wright; Rajabrata Sarkar; Anthony D. Sandler; Srinivasa R. Raghavan (Advanced Science)
Abstract The ability to “switch on” adhesion between a thin hydrogel and a biological tissue can be useful in biomedical applications such as surgery. One way to accomplish this is with an electric field, a phenomenon termed electroadhesion (EA). Here, it is shown that cationic gels can be adhered by EA to tissues across all of biology. This includes tissues from animals, including humans and other mammals; birds; fish; reptiles (e.g., lizards); amphibians (e.g., frogs), and invertebrates (e.g., shrimp, worms). Gels can also be adhered to soft tissues from plants, including fruit (e.g., plums) and vegetables (e.g; carrot). In all cases, EA is induced by a low electric field (DC, 10 V) applied for a short time (20 s). After the field is removed, the adhesion persists. The adhesion can also be reversed by applying the field with opposite polarity. In mammals, EA is strong for many tissues (e.g., arteries, muscles, and cornea), but not others (e.g., adipose, brain). Tissues with anisotropic structure show anisotropic adhesion strength by EA. The higher the concentration of anionic polymers in a tissue, the stronger its adhesion to cationic gels. This underscores that EA is mediated by the electrophoresis of chain segments across the gel‐tissue interface.